Influence of human factors on the uncertainties of refurbishment projects : a proposed conceptual approach - Ridzuan Yacob; Masran Saruwono; Zulhabri Ismail; Low, Sui Pheng (Penerbit Universiti Kebangsaan Malaysia, 2019)
The number of building refurbishment projects has increased significantly over the past few years in Malaysia. The key features of such projects are that these are unique, with high uncertainties especially when these involve structural modifications with sensitive, dangerous and difficult operations as well as the high number of building services involved. From many past studies, uncertainty has always been identified as one of the reasons for poor performance in such projects. This seems to be the case because few considerations were given to the human factor compared to the technical issues. This emphasis is however questionable in the real world. This conceptually based paper therefore aims to determine and understand the influence of human factor on the uncertainties of refurbishment projects. The method used for this study is based on a comprehensive review of related journal papers, book chapters and conference papers from 1997 to 2017. The exercise identified 146 articles initially. 57 papers were subsequently included for further analysis after screening and assessment for eligibility. This study concludes that the human impact element is indeed one of the most important factors that tends to influence the levels of uncertainties in building refurbishment projects. As a result, there is still room for improving the performance of building refurbishment projects. The findings of this study form the basis for an extended investigation to identify the effect of human factors on the uncertainties of building refurbishment projects in Malaysia.